Optimalisasi Kapabilitas Guru melalui E- Evaluation dan Media Ajar Storyline dalam Pembelajaran Berdiferensiasi di MAS Al-Husainy Kota Bima: Dampak pada Efektivitas Evaluasi Pembelajaran - Irawati, Ika; Annisah, Annisah; Ilyas, Ilyas; Meirawan, Deddyn (Jurnal Gema Ngabdi, 2025)
In the digital era, teachers are required to continuously enhance their capacity to integrate educational technology into the learning process. Interactive learning media and digital evaluation (e-evaluation) play an essential role in supporting differentiated learning. However, many private schools still rely on traditional approaches, such as paper-based tests, Google Forms, whiteboards, and PowerPoint. This condition highlights the need for digital teaching media and e-evaluation tools such as Articulate Storyline to improve learning quality and outcomes. This community service program was designed with four objectives: (1) to improve private school teachers’ skills in using technology, (2) to enhance their understanding of e-evaluation, (3) to strengthen their ability to apply digital learning media, and (4) to broaden their insights into designing assessments and learning media based on differentiated learning. The program employed presentations, demonstrations, and practical training, carried out through several stages: Focus Group Discussions (FGD), training and mentoring, monitoring, and evaluation. The outcomes indicate significant achievements: 95% of teachers actively participated, 83% gained competence in developing digital media with Storyline, and 80% understood the application of e-evaluation for differentiated learning. Furthermore, 90% of students obtained recognition in related courses such as Human-Computer Interaction, Teaching Strategies, and Learning Evaluation. Additional outputs include an e-evaluation guidebook, teacher certificates, visual posters, a published article in Gema Ngabdi Journal, media coverage, and a documented video on the university’s YouTube channel.